ChemInform Abstract: Formation of 2‐Cyano‐2‐siloxyvinylallenes via Cyanide‐Induced Brook Rearrangement in γ‐Bromo‐α, β, γ, δ‐unsaturated Acylsilanes. Issue 21 (May 2015) - Ando, Masafumi; Sasaki, Michiko; Miyashita, Izumi; Takeda, Kei
Abstract The γ‐bromo‐α, β, γ, δ‐unsaturated acylsilanes react with KCN under phase‐transfer conditions to yield 2‐cyano‐2‐siloxyvinylsilanes.